2019
DOI: 10.21475/poj.12.01.19.pt1773
|View full text |Cite
|
Sign up to set email alerts
|

Study of the allelopathic activity of Garcinia pedunculata Roxb

Abstract: The allelopathic properties of plants can be used as an alternative weed control method to reduce the use of synthetic herbicides. Accordingly, the present study was carried out to determine the allelopathic activity of Garcinia pedunculata. Six different concentrations of aqueous methanol extracts of G. pedunculata fruit were prepared and used to determine their effect on the growth of eight test plants: alfalfa (Medicago sativa L.), cress (Lepidum sativum L.), lettuce (Lactuca sativa L.), rapeseed (Brassica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…The phytotoxic activity increased with increasing extract concentration and varied among the target species. Our findings corroborate studies by other researchers [31][32][33], who showed the concentration-and test species-dependent growth-inhibitory effects of different plant extracts. These results indicated that the growth-inhibitory effect might be due to allelopathic substances within the plant extracts.…”
Section: Discussionsupporting
confidence: 93%
“…The phytotoxic activity increased with increasing extract concentration and varied among the target species. Our findings corroborate studies by other researchers [31][32][33], who showed the concentration-and test species-dependent growth-inhibitory effects of different plant extracts. These results indicated that the growth-inhibitory effect might be due to allelopathic substances within the plant extracts.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, J. adhatoda also had a rather good negative association extract concentration of shoot and root growth and the Pearson correlation coefficient in the net house environment ranged from −0.943 to −0.991 (p<0.01) (Supplementary Table 1 & 2). Our findings were confirmed by the similar findings described by the researchers (19).…”
Section: Effect Of the Aqueous Methanol And Aqueous Extracts Obtained From Leaves Of J Adhatoda On The Shoot And Root Length (Cm)supporting
confidence: 93%
“…Shoot and root lengths were found to decrease with increasing treatment concentration in all test species. The inhibitory effect of the extracts on test plants may be a range of mechanisms such as lower mitotic activity in growing parts of the plant, lower ion absorption rate, inhibition of photosynthetic respiration and malfunctions of enzyme activity (18,19). The root lengths of 2.58, 2.45, 2.42, 2.31 and 2.22 cm were found in cauliflower, broccoli, tomato, foxtail millet and barnyard grass respectively whereas, root lengths of 1.81, 1.72, 1.70, 0.39 and 0.37cm were observed with 0.1 gm DW e extract mL-1in the laboratory condition (Supplementary Fig.…”
Section: Effect Of the Aqueous Methanol And Aqueous Extracts Obtained From Leaves Of J Adhatoda On The Shoot And Root Length (Cm)mentioning
confidence: 99%
“…In addition, the results indicate that seedling length varied among the model plants, and the level of inhibition depended on the extract concentration (Figure 1). Similarly, several previous studies have also reported that the phytotoxic effect is concentration-dependent [48][49][50][51][52][53]. Moreover, many previous studies noted that test plant speciesʹ response varied depending on the types of phytotoxic substances [54].…”
Section: Biological Activity Of the Aqueous Methanol Extracts Of A Xylocarpa Leavesmentioning
confidence: 82%